(untitled) (Biological Sciences - PJSIR, 2000)
The natural population ofArtemia appeared inthe lastweekofOctoberfollowinga drop inthe average temperature (26°-33°C) by largescale hatching of cysts. It established rapidly byovo-viviparous modeof reproduction and acquired peak density of 13 individuals per literinNovember-December (20°-26°C)and disappeared during May-June(day temperature, 37°C and above). The optimal temperature regimefor sustenance and growth of population was23°-28°C. A widerange of salinity tolerance was observed butthe temperatureappeared to playa rolemoreimportantthan salinity incontrolling growth, survival, and reproduc- tion of Arternia in the saltworks of KorangiCreek.